Jane Jacobs is still here Jane Jacobs 100 Her legacy and relevance in the 21st Century - Rocco, Roberto (TU Delft Open, 2023)
On the occasion of Jane Jacobs' 100 anniversary, the chair of Spatial Planning and Strategy of the Delft University of Technology, together with the OTB Research Institute for the Built Environment and the Rotterdam Erasmus University College organised a two-day conference on Jane Jacob's legacy at TU Delft on 24-25 May 2016. This event was complemented one year later by a 'Jane Jacobs Year' closing event. We wished to celebrate the life and accomplishments of one of the most important urban thinkers of our time, someone who has influenced generations of designers and planners and others concerned with the built environment: the great Jane Jacobs. This volume contains a number of papers presented at the celebratory conference held at TU Delft in May 2016, with six tracks coordinated by guest scholars. Track 1: Jane Jacobs, ethics, and the just city Track 2: Jane Jacobs and Street Spaces - Streets as public places Track 3: Jane Jacobs and the dynamics of neighbourhoods Track 4: Jane Jacobs and the Reshaping old urban fabrics in Chinese cities Track 5: Jane Jacobs and organised complexity Track 6: Jane Jacobs and safety in public space